Some aspects of migration policy in Germany (Journal of Philosophy Culture and Political Science, 2019)
This article contains politological analysis of German modern migration policy, analyzes theoretical and application aspects of development of the German migration system based on national and international practice in the sphere of regulation of population mobility. Special attention is given to problems of integration of migrants. Keywords: migration, migration policy, migrant, political status of migrant.